An investigation on the impact of competition on the financial performance of MBC Accounting Services Private Limited - Mutsago, Tariro (Midlands State University, 2017)
Aim The aim of the study was to investigate the impact of competition on the financial performance of MBC Accounting Services (Pvt) Ltd. It was prompted by the noted decline in the annual profits and gradual decreases in the clientele base from the year 2013 to 2016 despite efforts by management to improve the financial performance. Methodology The study was conducted on a survey descriptive approach which uses quantitative and qualitative data collection methods. A census of 19 questionnaires were administered and 18 were provided for analysis yielding a response rate of 94, 74%.Six interviews were scheduled and successfully conducted. Data was presented through tables and analyzed using the measures of central tendency. To determine the relationship between competition and financial performance, linear regression was used to determine the hypothesis. Key Findings Major research findings indicated that the rivalry amongst existing firms, threat of new entrants and the bargaining power of supplier were the majors forces influencing the degree of industrial competiton. Besides these forces the company was affected by firm size. However challenges were being faced in adapting to the competitive environment which includes lack of managerial support which demotivated the moral of employees. Key recommendations The researcher suggested recommendations were that MBC management should have continuous employee training programmes so that they are abreast with changes in the macro-economic environment thus successfully adapt to the competitive environment. Originality The research showed that besides competition, there are more important mediating variables in the influence on financial performance and management should take an active role.